Diagnosis and Management of Osteosarcopenia - Jersivindo Ranazeri; Rose Dinda Martini; Mulyana, Roza; Fandi Triansyah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Osteosarcopenia is a syndrome defined as a combination of low bone density and muscle mass as well as decreased strength and/or functional capacity. Osteoporosis and sarcopenia often coexist in the elderly, leading to a significantly worse prognosis. The epidemiology of osteosarcopenia is quite limited because the term is still new. Osteosarcopenia is more common in women than men and in malnutrition. Age-related immunological changes such as hormonal imbalance, chronic inflammation, increased oxidative stress, imbalance in protein metabolism, increased fat deposition, decreased physical activity, and poor nutritional status contribute to sarcopenia. Decreased bone density in osteoporosis can occur due to an imbalance between osteoblasts and osteoclasts. The diagnosis of osteosarcopenia is made based on the presence of osteoporosis and sarcopenia. Instrument strength, assistance with walking, rising from a chair, climbing stairs, and falls (SARC–F) are recommended for assessing sarcopenia and the fracture risk assessment tool (FRAX) for the risk of osteoporotic fracture. Management of osteosarcopenia is carried out holistically, including management of osteoporosis and sarcopenia both non-pharmacologically and pharmacologically.